Fostering motivation in the engagement of volunteer workers: an analysis of volunteers in humanitarian organisations in Zimbabwe - Mutambara, Julia; Mutambara, S (Scholarlink Research Institute Journals, 2016)
The aim of the study was to look at the factors that motivate volunteers` engagement in voluntary work in Non Governmental Organisations (NGOs) in Zimbabwe. A descriptive survey was done to answer the research questions. Questionnaires were self administered to 60 volunteers sampled from two NGOs in Zimbabwe. Two focus group discussions with 6 volunteers from each organisation were also carried out. SPSS was used to analyse the quantitative data and content analysis was used to analyse qualitative data from focus group discussions. This involved extraction of major themes and which were then merged with the quantitative data that was obtained. The results revealed that volunteers need to be formally contracted and nurtured and that they were motivated by material rewards, trainings and recognition.